2017
DOI: 10.3897/compcytogen.v11i2.12070
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of chromosomes in the Palaearctic bush-crickets of tribe Pholidopterini (Orthoptera, Tettigoniinae)

Abstract: The present study focused on the evolution of the karyotype in four genera of the tribe Pholidopterini: Eupholidoptera Mařan, 1953, Parapholidoptera Mařan, 1953, Pholidoptera Wesmaël, 1838, Uvarovistia Mařan, 1953. Chromosomes were analyzed using fluorescence in situ hybridization (FISH) with 18S rDNA and (TTAGG)n telomeric probes, and classical techniques, such as C-banding, silver impregnation and fluorochrome DAPI/CMA3 staining. Most species retained the ancestral diploid chromosome number 2n = 31 (male) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…A similar type of translocation is reported in some other species of Tettigoniinae (e.g. Grzywacz et al, 2017a;Warchałowska-Śliwa et al, 2005Warchałowska-Śliwa et al, , 2017. In addition, the present and previous studies indicate that the karyotypes of Tettigonia are stable and there are no changes in the chromosome number and general morphology of the X chromosome in this genus.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A similar type of translocation is reported in some other species of Tettigoniinae (e.g. Grzywacz et al, 2017a;Warchałowska-Śliwa et al, 2005Warchałowska-Śliwa et al, , 2017. In addition, the present and previous studies indicate that the karyotypes of Tettigonia are stable and there are no changes in the chromosome number and general morphology of the X chromosome in this genus.…”
Section: Discussionsupporting
confidence: 90%
“…A single bivalent carrying the 18S rDNA cluster, but in the interstitial or paracentromeric regions, is reported in other tettigoniids, e.g. in European Platycleidini (Grzywacz et al, 2017a) and Pholidopterini (Warchałowska-Śliwa et al, 2017). Furthermore, one active NOR appears to be a typical feature of karyotypes of European Tettigoniinae (Warchałowska-Śliwa et al, 2005).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Probably, a lack of tDNA-FISH signal in some chromosomes could explain the low number of telomeric copies. Similar results have been reported in other Orthoptera species [Warchałowska-Śliwa et al, 2013[Warchałowska-Śliwa et al, , 2017. Previous studies have suggested that (TTAGG) n was a phylogenetically ancestral telomere motif in Hexapoda but was lost independently in different groups [Sahara et al, 1999;Frydrychová et al, 2004].…”
Section: Discussionsupporting
confidence: 78%